2010
DOI: 10.5194/nhess-10-305-2010
|View full text |Cite
|
Sign up to set email alerts
|

Combining ASTER multispectral imagery analysis and support vector machines for rapid and cost-effective post-fire assessment: a case study from the Greek wildland fires of 2007

Abstract: Abstract. Remote sensing is increasingly being used as a cost-effective and practical solution for the rapid evaluation of impacts from wildland fires. The present study investigates the use of the support vector machine (SVM) classification method with multispectral data from the Advanced Spectral Emission and Reflection Radiometer (ASTER) for obtaining a rapid and cost effective post-fire assessment in a Mediterranean setting. A further objective is to perform a detailed intercomparison of available burnt ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 60 publications
1
20
0
Order By: Relevance
“…Furthermore, in a study over a site in Greece, Koutsias et al (2012) reported an increase in the reflectance of burned surfaces observed in the middle-infrared region (2.08-2.35 lm or band 7) of the Landsat TM sensor (which corresponds to ASTER bands 5, 6, 7 and 8) because of changes in water content. The improving incidence of ASTER SWIR band inclusion to the classification process was also reported in another study by (Petropoulos et al 2010a), in which the authors concluded that the benefit from advanced land imager (ALI) sensor use in burned area extraction appears to be partially due to its higher number of spectral SWIR bands. Findings presented herein are also in close agreement to those reported by others who have explored the use of either the ML or the SVMs classifier in burn scar extraction from multispectral imagery.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Furthermore, in a study over a site in Greece, Koutsias et al (2012) reported an increase in the reflectance of burned surfaces observed in the middle-infrared region (2.08-2.35 lm or band 7) of the Landsat TM sensor (which corresponds to ASTER bands 5, 6, 7 and 8) because of changes in water content. The improving incidence of ASTER SWIR band inclusion to the classification process was also reported in another study by (Petropoulos et al 2010a), in which the authors concluded that the benefit from advanced land imager (ALI) sensor use in burned area extraction appears to be partially due to its higher number of spectral SWIR bands. Findings presented herein are also in close agreement to those reported by others who have explored the use of either the ML or the SVMs classifier in burn scar extraction from multispectral imagery.…”
Section: Discussionmentioning
confidence: 64%
“…Findings presented herein are also in close agreement to those reported by others who have explored the use of either the ML or the SVMs classifier in burn scar extraction from multispectral imagery. For example, Petropoulos et al (2010a) combined ASTER and Landsat TM data, respectively, with the SVMs in mapping the extent of the burned area of the same fire event. The results presented herein outperformed the performance of the artificial neural network (ANN) and spectral angle mapper (SAM) classifiers when combined with the Landsat imagery reported to that study by the authors.…”
Section: Discussionmentioning
confidence: 99%
“…The reason behind this selection is its better performance in previous studies (Colgan et al, 2012;Huang et al, 2002;Petropoulos et al, 2010). Moreover, this kernel needs less parameter for tuning compared to the other ones (2 parameters (cost and sigma) compared to 4 parameters in polynomial and 3 in sigmoid kernels).…”
Section: Svm Methodsmentioning
confidence: 99%
“…Different types of remote sensing data have been exploited for more than 20 yr in performing various fire analysis investigations, including mapping the extent of burnt areas (e.g. Trigg and Roy, 2007;Roy and Boschetti, 2009;Petropoulos et al, 2010).…”
Section: P Kalivas Et Al: An Intercomparison Of Burnt Area Estimmentioning
confidence: 99%